An analysis and evaluation of food waste management processes and the role on food waste at consumer level within a quick service restaurant in Parkhurst, Johannesburg. - Singo, Mpho Cindy (The IIE, 2020)
The research analysed and evaluated the role food waste management processes have on food waste at consumer level, within the context of a quick service restaurant (QSR), in Parkhurst, Johannesburg. The study reviewed literature on food waste management within a QSR supply chain and food packaging and waste within the entire supply chain process. The main intention of the study was to analyse and evaluate food waste management processes and the role it has on consumer food waste. Further to this, the study identified possible strategies to minimise food waste at both QSR and consumer level, to achieve the meaningful brand status. A qualitative case study approach was deployed to collect data. This was conducted through in-depth interviews with staff members and consumers of Rockets Parkhurst. The conceptual development of the study lied on the hermeneutics and phenomenology theories within the inductive interpretivist paradigm. These theories “attempt to understand and describe meaningful social actions, experiences, and human nature. The selected research methodology and paradigm was applicable because the study aimed to analyse and evaluate food waste management processes and the role it has on food waste at consumer level. Therefore, the study required a more inductive, interpretive approach to allow the researcher to obtain a contextual representation of how the brand and its consumers experience the research problem.
Keywords: Food packaging; Supply chain management; Food loss and waste management